Big Five Personality Traits Among Lecturers and Job Satisfaction: A Case Study of Private Universities in Bogor City - Rully, Tutus; Anoesyirwan,; Hari Muharram, (Journal of Social Transformation and Regional Development, 2023)
Personality is a unique psychological aspect possessed by each individual and describes how the individual communicates with his environment. In the context of this research, we will focus on the five main dimensions of personality that are often considered, namely extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience. Understanding how these big five personality dimensions can influence lecturer job satisfaction can provide valuable insights for the management and development of human resources in higher education. This research uses a descriptive verification type, where analytical testing is obtained through a representation of the characteristics of several research variables. Thus, the main aim of this research is to explore more deeply the relationship between personality and job satisfaction of lecturers in higher education with SEM-Lisrel 8.8.